Improvement of indices of immunity of hiv-infected individuals with chronic toxoplasmosis infestation and insufficient immune reconstitution of antiretroviral therapy through the using of ribonucleic acid medication - Hryzhak, Ihor; Dykyi, Bohdan; Pryshliak, Alexandra; Ostiak, Roman; Tkachuk, Zenovii (ScienceRise: Medical Science, 2017)
Aim of the work. To study the possibility of additional correction of immunologic imbalance by ribonucleic acid medication in HIV-infected persons, infested by Toxoplasma gondii, who receive antiretroviral therapy and did not attain immunoreconstitution. Methods of research. 60 HIV-infected persons, seropositive as to Toxoplasma gondii infestation were examined. All patients received antiretroviral therapy (ART) during no less than 6 months, but the number of СD4+Т-lymphocytes in them did not exceed 350 kl/mcl of blood. The immune-enzyme method was used for determination of titres of specific anti-toxoplasmosis IgG and IgМ; general IgM, IgA, IgG, and also IL-2, IL-4, IL-10, INF-γ, TNF-2α. The number of CD4+ Т –lymphocytes was determined by cytofluorimetric method. The one group of 30 persons received ribonucleic acid medication in dose 1500 mg a day during 1-st month and during 2-d and 3-d month - 750 mg a day; other group of 30 patients did not receive medication. The statistical processing was carried out in Exсel, using Student t-criterion. Results. In HIV-infected persons with toxoplasmosis infestation comparing with healthy ones were revealed the increased levels of proinflammatory cytokines - TNF-α (2,47±0,11 pg/ml against 1,90±0,04 pg/ml, P<0,001), INF-γ (10,82±0,38 pg/ml against 4,13±0,12 pg/ml, P<0,001), and anti-inflammatory ones IL -4 (1,74±0,08 pg/ml against 0,81±0,09pg/ml, P<0,001) and IL-10 (11,64±0,31 pg/ml against 6,70±0,13 pg/ml, P<0,001). The persons, who received ribonucleic acid medication comparing with ones, who did not receive it, demonstrated the increase of IL-2 (2,83±0,11 pg/ml against 2,28±0,11 pg/ml, P<0,001) and INF-γ (11,29±0,25 pg/ml against 9,98±0,26pg/ml, P<0,001), instead of it TNF-α decreased (2,25±0,08 pg/ml against 2,50±0,09 pg/ml, P<0,05). After 3-d month of treatment IL-10 (7,73±0,22 pg/ml against 9,83±0,30 pg/ml, P<0,001), TNF-α (2,23±0,10 pg/ml against 2,53±0,09 pg/ml, P<0,05)levels decreased, and INF-γ increased (10,37±0,11 pg/ml against 9,86±0,20 pg/ml, P<0,05). In the group of patients, who did not receive medication the relapse of toxoplasmatic encephalitis appeared in two cases. Conclusion. It was established, that HIV-infected persons, with Toxoplasma gondii infestation, who took ART but with insufficient immunoreconstruction, demonstrated the increased levels of several proinflammatory (TNF-α, INF-γ) and anti-inflammatory (IL-4, IL-10) cytokines. After the treatment using ribonucleic acid medication the levels of СD4 + Т-lymphocytes, IL-2 and INF-γ increased and IL-10 decreased that eliminated the risk of toxoplasmatic encephalitis development